Antibodies against Leptospira spp. in bovine serum samples from several Brazilian states analyzed in the period from 2007 to 2015 - Furquim, M.e.c. [UNESP]; Santos, R.f. [UNESP]; Mathias, L.a. [UNESP] (Universidade Federal de Minas Gerais, Escola de Veterinária, 2021)
Bovine leptospirosis assumes great economic importance since it affects several production aspects. Therefore, knowledge about the occurrence and distribution of this disease is fundamental to adopt the correct prevention measures. The present study aimed to evaluate the frequency of anti-Leptospira spp. antibodies in 24,483 bovine serum samples received between 2007 to 2015 from 21 Brazilian states. Of these, 8,643 (35.3%) were reagents in the microscopic agglutination test to one or more serovars of Leptospira spp. The most frequent serovars were Wolffi (61.47%), Tarassovi (9.62%) and Pomona (7.20%). Hardjo serovar presented a prevalence of 6.27%. Among the 21 states analyzed, the State of Pernambuco had the highest frequency with 88.24% and the State of São Paulo was the origin of the largest number of analyzed samples (13,838), with a frequency of 31.54% of reagents. The results demonstrate a high exposure to several serovars of Leptospira spp. in bovine species in Brazilian states, showing the importance of adopting prophylactic measures in order to reduce the risk of infection in this specie.

Com o objetivo de avaliar a frequência de anticorpos anti-Leptospira spp., foram analisadas 24.483 amostras de soro sanguíneo bovino, provenientes de 21 estados brasileiros, recebidas no período de 2007 a 2015. Destas, 8.643 (35,3%) foram reagentes no teste de soroaglutinação microscópica a uma ou mais sorovariedades de Leptospira spp., e as sorovariedades com maior frequência foram Wolffi (61,47%), Tarassovi (9,62%) e Pomona (7,20%). A sorovariedade Hardjo apresentou prevalência de 6,27%. Entre os 21 estados analisados, o estado de Pernambuco apresentou a maior frequência, com 88,24%, e o estado de São Paulo foi a origem do maior número de amostras para análise, 13.838, com frequência de 31,54% de reagentes.
[Anticorpos contra Leptospira spp. em amostra de soro bovino de diversos estados brasileiros analisados no período entre 2007 e 2015]
Keywords: epidemiology; leptospirosis; Microscopic Agglutination Test (MAT); vaccination; leptospirose; teste de soroaglutinação microscópica (MAT); epidemiologia; vacinação